2018
DOI: 10.1016/j.cmet.2018.02.007
|View full text |Cite
|
Sign up to set email alerts
|

Visceral Adipose Tissue Immune Homeostasis Is Regulated by the Crosstalk between Adipocytes and Dendritic Cell Subsets

Abstract: SummaryVisceral adipose tissue (VAT) has multiple roles in orchestrating whole-body energy homeostasis. In addition, VAT is now considered an immune site harboring an array of innate and adaptive immune cells with a direct role in immune surveillance and host defense. We report that conventional dendritic cells (cDCs) in VAT acquire a tolerogenic phenotype through upregulation of pathways involved in adipocyte differentiation. While activation of the Wnt/β-catenin pathway in cDC1 DCs induces IL-10 production, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
103
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(106 citation statements)
references
References 56 publications
1
103
0
2
Order By: Relevance
“…38,39 Although ATDCs increase quantitatively along with ATMs in obesity, 39,95,96 the contribution of ATDCs to meta-inflammation and IR remains not completely understood. 97 Based on certain reports, human CD11c + CD1c + and mouse CD11c high F4/80 low ATDCs have been considered as an inflammatory subtype of DCs in AT in obesity-associated IR. 39,91 Similarly, an increase in ATDCs has been positively correlated with high BMI in humans.…”
Section: T-cell Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…38,39 Although ATDCs increase quantitatively along with ATMs in obesity, 39,95,96 the contribution of ATDCs to meta-inflammation and IR remains not completely understood. 97 Based on certain reports, human CD11c + CD1c + and mouse CD11c high F4/80 low ATDCs have been considered as an inflammatory subtype of DCs in AT in obesity-associated IR. 39,91 Similarly, an increase in ATDCs has been positively correlated with high BMI in humans.…”
Section: T-cell Activationmentioning
confidence: 99%
“…In addition, lack of b-catenin in ATDCs is associated with decreased IL-10 levels and suppressed Treg recruitment to AT leading to more inflammation. 97 Based on certain reports, human CD11c + CD1c + and mouse CD11c high F4/80 low ATDCs have been considered as an inflammatory subtype of DCs in AT in obesity-associated IR. 89 In DIO models, a population of CDllc high F4/80 neg ATDCs has been shown to be responsible for the induction of both Th1 and Th17 cells, whereas CDllc high F4/80 low ATDCs for the differentiation of Th17 cells.…”
Section: Adipose Tissue Dendritic Cellsmentioning
confidence: 99%
“…After receiving the activation signal associated with the antigen, DCs produce cytokines and inflammatory mediators such as TNFα, IL-6, IL-11, IL-12, and IL-23, which, in turn, induce the proliferation of allogeneic T cells and differentiate them to the Th17 and Th1 subtypes [40]. However, in visceral adipose tissue (VAT), DCs suppress inflammation by activating the β-catenin and PPARγ pathways, which are important regulatory mechanisms for fat expansion [41]. Subsequently, β-catenin activation triggers PI3K/Akt that, in turn, induces IL-10 production and inhibits IL-6 secretion [42].…”
Section: Dendritic Cells (Dcs)mentioning
confidence: 99%
“…observed increased permeability and vessel fibrosis in CCR7 −/− mice; however, on recovery of CCR7 in cDCs the development of fibrosis was reversed. Antigen sampling is not limited to lymphatic vessels as VAT‐cDCs are also observed in close proximity to blood vessels . These studies suggest that VAT‐cDCs are strategically located close to vessels to sample antigen and maintain vessel integrity, therefore contributing to the immune surveillance of neighbouring tissues.…”
Section: Adipose Tissue Dendritic Cells In Steady‐statementioning
confidence: 90%
“…VAT‐cDC cross‐talk appears to modulate not only pre‐adipocyte differentiation but also adipocyte function. Our work recently demonstrated that cDCs in VAT acquire a tolerogenic phenotype under physiological conditions by up‐regulating pathways involved in adipocyte differentiation . In VAT, the Wnt/ β ‐catenin pathway keeps pre‐adipocyte differentiation in check, while PPAR γ signalling allows adipocyte expansion to buffer excess of nutrients.…”
Section: Adipose Tissue Dendritic Cells In Steady‐statementioning
confidence: 95%